Forever Amber - Winsor, Kathleen (Chicago Review Press, 2000)
"Abandoned pregnant and penniless on the teeming streets of London, sixteen-year-old Amber St. Clare uses her wits, beauty, and courage to clinb to the highest position a woman could achieve in Restoration England--that of favorite mistress of the Merry Monarch, Charles II. ... But throughout her trials and escapades, she remains, in her heart, true to the one man she really loves, the one man she can never have."--Cover.